(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
This paper explores the evolving landscape of English language methodology and the integration of technology in language teaching. It examines various pedagogical approaches, including communicative language teaching, task-based learning, and content-based instruction, analyzing their effectiveness in promoting language acquisition. Furthermore, it delves into the role of technology in enhancing language learning, discussing the use of computer-assisted language learning (CALL), mobile-assisted language learning (MALL), and online learning platforms. The paper investigates the benefits and challenges of integrating technology into English language classrooms, highlighting the importance of teacher training and professional development in this area. The discussion emphasizes the need for a blended approach, combining effective teaching methodologies with appropriate technology to create engaging and effective learning environments. The research aims to provide an overview of the current trends and insights into how technology can be leveraged to improve language teaching and learning outcomes.